Pengaruh Celebrity Endorsement dan E-Wom terhadap Repurchase Intention pada Produk Scarlett dengan Brand Image sebagai Variabel Mediasi - Winandri, Azzahra Vania Rahma (Prosiding University Research Colloquium, 2022)
This study aims to analyze and discuss the effect of celebrity endorsement and E-WOM on repurchase intention on Scarlett products with brand image as a mediating variable. The population in this study were students who were consumers of Scarlett products in the city of Surakarta with a sample of 160 respondents. Data collection techniques through the distribution of questionnaires. Data analysis in this study used Smart PLS version 3.0. The sampling technique in this study uses purposive sampling and data testing techniques used in this study include the outer model consisting of convergent validity, discriminant validity, composite reliability, Cronbach’s alpha and multicollinearity tests as well as the inner model consisting of coefficient determination, goodness of fit, effect size test (f2), and hypothesis testing. The results of this study indicate that celebrity endorsement has a significant effect on brand image, E-WOM has a significant effect on brand image, brand image has a significant effect on repurchase intention, celebrity endorsement has a significant effect on repurchase intention, E-WOM has no significant effect on repurchase intention, brand image role in mediating between celebrity endorsement and repurchase intention, brand image mediating role between E-WOM and repurchase intention.